PENINGKATAN KINERJA GURU SDN 123 BABAKAN PRIANGAN DALAM PEMBELAJARAN DI KELAS MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK - Yeyet Nurhayati (GoAcademica Research dan Publishing, 2022)
The purpose of this study was to describe the improvement in the ability of classroom teachers in managing learning at 123 Babakan Priangan State Elementary School, Bandung City after supervision / guidance actions were carried out. This School Action Research was carried out at 123 Babakan Priangan State Elementary School, Bandung City. The type of action in this research is in the form of real action, namely guiding teachers in carrying out learning activities through academic supervision. The research was conducted in the first semester, precisely in July-November 2021. The subject of this school action research was the class teacher at 123 Babakan Priangan State Elementary School with a total of 6 teachers. The results showed that teacher performance increased after taking actions in the form of collaborative educational supervision periodically from cycle I to cycle II. These improvements include improvements in preparing lesson plans, implementing learning, assessing learning achievement, carrying out follow-up assessments of student achievement.